Does the augmentation of trauma informed Hatha Yoga increase the effect of dialectical behavior therapy for substance use disorders on psychopathological strain of patients with Borderline personality disorder and comorbid substance use disorder?: Results of a quasi-experimental study - Riegler, Alisa; Bumb, Jan Malte; Wisch, Christian; Schuster, Rilana; Reinhard, Iris; Hoffmann, Sabine; Frischknecht, Ulrich; Enning, Frank; Schmahl, Christian; Kiefer, Falk; Koopmann, Anne (European addiction research, 2023)
Background: Borderline personality disorder (BPD) is one of the most common personality disorders among persons with substance use disorders (SUDs) and is characterized by severe clinical symptoms. The aim of this study was to investigate if the effect of dialectical behavior therapy for substance use disorders (DBT-S) inpatient treatment on psychopathological symptom load in patients suffering from both BPD and SUD can be augmented by weekly 60-min “Trauma Informed Hatha Yoga” sessions. Materials and Methods: Thirty-nine patients suffering from comorbid BPD and SUD were consecutively in time included in this quasi-experimental pilot study (first intervention then control group). In the intervention group, weekly Trauma Informed Hatha Yoga sessions were added to standard DBT-S for 8 weeks. The participants of the control group received standard DBT-S. All participants completed several self-report questionnaires to assess symptoms of depression, anxiety, symptoms of BPD, and their subjective stress perception at three points in time during the study course. Results: A repeated measures analysis of variance with patients’ psychopharmacological medication as covariate revealed a significant main effect of time for each of the psychometric scales (State and Trait Anxiety Inventory subscale for state anxiety [STAI-S] p = 0.001, Beck Depression Inventory [BDI] p < 0.001; Borderline Symptom List 23 [BSL] p = 0.036) indicating that the psychopathological symptom load of the patients was significantly lower at the end of the DBT-S therapy compared to the beginning in both study groups. Moreover, there was a significant interaction effect of group*time on the psychometric scales STAI-T (subscale for trait anxiety) sum score (p = 0.010) and the sum score of the Perceived Stress Scale (PSS) (p = 0.043). This was expressed by the fact that the participants of the intervention group showed a significant reduction of the STAI-T sum score as well as the sum score of the Perceived Stress Scale (PSS), while the control group did not. Due to the exploratory nature of this study, correction for multiple testing was omitted. Conclusion: Although they are very preliminary, our results suggest that practicing Trauma Informed Hatha Yoga on a regular basis in addition to DBT-S inpatient treatment seems to reduce the level of trait anxiety and perceived stress significantly more than DBT-S inpatient treatment alone. Nevertheless, the effectiveness of Trauma Informed Hatha Yoga in reducing trait anxiety and perceived stress in patients suffering from SUD und BPD must be tested in large randomized controlled trials.
Online veröffentlicht: 10. Oktober 2022
Gesehen am 16.07.2024